Adsorption of antibiotics onto microparticles and its effect on marine microbial growth and death - Goh, Jamine Ying Min (Nanyang Technological University, 2021)
Antibiotic resistance is becoming a major global concern as it prevents effective treatment of diseases. The spread is coupled by microplastics, which serves as a reservoir for the spread of antibiotic resistance genes (ARGs) as biofilm formation and the adsorption of antibiotics on these surfaces allow attached microbes to gain ARGs. One of the main causes is improper disposal methods by wastewater treatment plants (WWTPs), which serves as a reservoir for microplastics, antibiotics and antibiotic-resistant microbes. This study aims to examine: whether microplastics influence marine microbial death at different concentrations of certain antibiotics commonly found in the ocean; and the behaviour of antibiotic adsorption onto microplastics and its effect on microbial cell death. Clay was used as another microparticle in this experiment to examine whether differences in microparticles influenced adsorption behaviour and microbial growth and death. This study showed that increases in the concentration of antibiotic increased the amount of antibiotic adsorbed onto its surface. However, the amount adsorbed is limited by the surface area of the microparticle. Zeta potential measurements were statistically different between microplastics and clay with adsorbed antibiotics. Microplastics were shown to potentially contribute to better microbial growth in low antibiotic concentrations.